2014
DOI: 10.1002/jctb.4447
|View full text |Cite
|
Sign up to set email alerts
|

Application of process analytical technology for downstream purification of biotherapeutics

Abstract: The concept of Process Analytical Technology (PAT) introduced by the US FDA has received a lot of attention lately. The use of such a scheme ensures robust process performance over the entire life cycle of the product and consistent product quality at the end of the manufacturing process. Successful implementation of PAT requires use of high resolution, orthogonal analytical tools that are able to measure the critical quality attributes (CQA) of the raw materials and in‐process materials with the aim of ensuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…and product related impurities (e.g., aggregates, fragments, clipped species, etc.). Each purification step is capable of removing one or more classes of impurities 53, 54. Downstream processing usually encompasses three main stages, namely (i) initial recovery (extraction or isolation), (ii) purification (removal of most contaminants), and (iii) polishing (removal of specified contaminants and unwanted forms of the target biomolecule that may have formed during isolation and purification) 53, 55, 56…”
Section: Downstream Process: Isolation and Purification Of Biophamacementioning
confidence: 99%
“…and product related impurities (e.g., aggregates, fragments, clipped species, etc.). Each purification step is capable of removing one or more classes of impurities 53, 54. Downstream processing usually encompasses three main stages, namely (i) initial recovery (extraction or isolation), (ii) purification (removal of most contaminants), and (iii) polishing (removal of specified contaminants and unwanted forms of the target biomolecule that may have formed during isolation and purification) 53, 55, 56…”
Section: Downstream Process: Isolation and Purification Of Biophamacementioning
confidence: 99%
“…Several examples of successful implementation of advanced process analytical technologies (PATs) in upstream processing (USP) of biopharmaceuticals have been reported in the literature . However, the application of on‐line or at‐line monitoring tools for downstream processing (DSP), and in particular for chromatography, is less common and only few examples have been reported . Challenging requirements like a high sensitivity, fast response time, high accuracy, robustness, wide dynamic range, and low limit of detection (LOD) with minor recalibration needs make the implementation of on‐line monitoring techniques in DSP difficult .…”
Section: Introductionmentioning
confidence: 99%
“…Challenging requirements like a high sensitivity, fast response time, high accuracy, robustness, wide dynamic range, and low limit of detection (LOD) with minor recalibration needs make the implementation of on‐line monitoring techniques in DSP difficult . Extensive reviews showcase available monitoring techniques and applications in DSP . Sensors for pH, conductivity, pressure, mass flow, optical density, and single wavelength UV spectroscopy are widely implemented in chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…The use of such a scheme ensures robust process performance over the entire lifecycle of the product and consistent product quality at the end of the manufacturing process. There have been various case studies reported where PAT has been successfully implemented for various downstream unit operations like protein refolding, filtration, inline mixing, protein pegylation, viral inactivation, and process chromatography . Currently, various techniques such as UV spectroscopy, HPLC, and mass spectroscopy are available to monitor column effluent and provide useful information about product purity and impurity clearance .…”
Section: Introductionmentioning
confidence: 99%